IDENTIFIKASI SISTEM KONTROL KECEPATAN DENGAN SPEED CAMERA DAN PENERAPAN SANKSI YANG TEPAT - , AFRIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Global Road Safety Partnership based on speed management manual states that the speed is the biggest factor causing the accident. Decreased speed management strategy has been applied include: installation of road hump, rumble strips, installing signs and markings. But it is not yet able to reduce significantly the speed limit violation. A recent study by Arif Anwar (2010) reports the assessment of the implementation of speed cameras and the determination of the appropriate penalty system to increase the level of safety of road users. The study was conducted to determine the user's understanding of the maximum speed limit speed camera selection and application of appropriate sanctions. The data was collected using a questionnaire to the road users in Yogyakarta and Purbaleunyi Highways as the object of research. The population in this research is the minimum driver ages of 17 years because they are assumed have a grasp of the law. Descriptive statistics are used to process the data from the questionnaire include the user's understanding of the speed limit, the understanding of the sanctions applicable under the law as well as the selection of appropriate sanctions and could deter road users. The analysis is used to determine the ranking of the main reasons drivers breaking the speed limit The analysis showed that a low level of understanding of road users to the speed limit as well as an understanding of the applicable sanctions under the law. The value of fines can deter road users is Rp.200.000 for motorcycle users and Rp. 500,000 for car users. Both road users in the city of Yogyakarta and the Purbaleunyi Highways agree with the installation of speed cameras, along with oversight and penalties. The three main reasons of road users breaking the speed limit in the city of Yogyakarta and Purbaleunyi are in a rush condition, time is more important than speed, and no police guard / patrol. Type of speed camera can be used in accordance with the type of road.